Corporate Social Responsibility (CSR) in Sharia Accounting Perspective: Challenges and Opportunities Towards Sustainability - Nugroho, Lucky; Chaniago, Nuraini; Firdayetti, Firdayetti; Pratiwi, Futri Alif; Aurelia, Fadia Nazwah (Baca Dulu Publisher, 2024)
From the perspective of Sharia Accounting, Corporate Social Responsibility (CSR) offers a holistic approach that focuses on financial gain and includes the values of fairness, transparency, and social responsibility. However, the low levels of sharia-based CSR disclosure and lack of understanding of Maqasid Sharia indicate a gap between expectations and practices in the field. This study aims to analyze the application of Sharia Accounting principles in CSR measurement and reporting, identify the challenges faced, and provide strategic recommendations to improve its implementation. This study uses a descriptive qualitative method with a secondary data analysis approach, including academic literature, journal articles, and policy documents. The study's findings show that integrating CSR with Sharia Accounting requires a strong commitment from the company, especially in Maqasid Sharia-based measurement and reporting through Islamic Social Reporting (ISR). The main obstacles include limited human resources, lack of sharia CSR measurement standards, and organizational culture challenges. The results of this study confirm that the implementation of sharia-based CSR not only improves the company's reputation but also strengthens relationships with stakeholders through programs oriented to social and environmental welfare. The implications of this study provide practical guidance for Sharia companies to improve CSR transparency and accountability, as well as offer the latest in the form of developing a Maqasid Sharia-based CSR index that can measure the company's contribution holistically.